2021
DOI: 10.3390/app11020509
|View full text |Cite
|
Sign up to set email alerts
|

Design and Manufacture of Composite Landing Gear for a Light Unmanned Aerial Vehicle

Abstract: Unmanned aerial vehicles (UAVs) have become popular for military applications as well as for use in structural inspection, weather monitoring, and festival demonstrations. Suitable landing gears to ensure that the UAV can take off and land safely are important when the price of the cargo and UAV increase. A lightweight and high-strength landing gear is desirable to overcome accidents during service. Composite materials are a promising, excellent solution for this purpose. This study demonstrated the design, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[87], low-level swept field tests were employed to analyze the variations in shielding effectiveness among different materials, including carbon fiber composites and Shell shielding involves using materials with electromagnetic shielding or absorbing properties for the UAV's outer shell to minimize the transmission of EMI to the internal system. Commonly used materials in UAV shell manufacturing include carbon fiber composites, glass fiber composites, and plastics, chosen for their lightweight characteristics [83]. While these materials may have excellent mechanical properties, they often lack sufficient electrical conductivity to effectively shield against electromagnetic waves.…”
Section: Shielding Protectionmentioning
confidence: 99%
“…[87], low-level swept field tests were employed to analyze the variations in shielding effectiveness among different materials, including carbon fiber composites and Shell shielding involves using materials with electromagnetic shielding or absorbing properties for the UAV's outer shell to minimize the transmission of EMI to the internal system. Commonly used materials in UAV shell manufacturing include carbon fiber composites, glass fiber composites, and plastics, chosen for their lightweight characteristics [83]. While these materials may have excellent mechanical properties, they often lack sufficient electrical conductivity to effectively shield against electromagnetic waves.…”
Section: Shielding Protectionmentioning
confidence: 99%
“…Carbon fiber reinforced composites have gained widespread adoption in various industries, including vehicle transportation [ 1 , 2 ], military equipment [ 3 , 4 ], and aerospace [ 5 , 6 ], owing to their inherent benefits such as a high, specific strength and stiffness. However, the utilization of carbon fiber composites inevitably exposes them to low-velocity impact loads during operational usage, which can result in concealed internal damage and a notable degradation in the mechanical properties of the structure [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retractable or adjustable landing gear allows for unobstructed shots or videos with increased aerodynamic efficiency which is discussed by Huang in [6]. Liang, Chin, Sun, and Wang [7] implemented skid landing gear in UAV because of its lightweight and suitability for confined spaces. Campi, Cruciani, Maradei, and Feliziani [8] studied the dynamics of fixed landing gear in larger drones for rough terrains and found that landing of UAVs on flat surfaces is stable than on rough terrains.…”
Section: Introductionmentioning
confidence: 99%